In the Ant's school of wisdom : a holistic African - South African reading of Proverbs 6 : 6 - 11 - Masenya, Madipoane (Old Testament essays, 2015)
Committed to the ethic of industry, also, possibly persuaded by the precarious context of the production of the text of Prov 1-9, the wisdom teacher persuades his (male) students to watch and learn from the ways of the ant (nemalâ). The nemalâ can be regarded as one of the lowest members of the created species. Apart from the optimistic wisdom mentality embedded within Prov 6 : 6 - 11, noteworthy is also the inter-connectedness between human beings and nature. The latter reveals the holistic outlook which typified biblical Israel, including the members of the post-exilic community in Yehud. Research on the wisdom underlying both the HB proverbs and selected African (Northern Sotho/Pedi) proverbs, has revealed apparent resemblances between Israelite and African world views. If Prov 6 : 6 - 11 is read from an African-South African holistic point of view, which insights might be gained from the text regarding the interconnectedness between human beings and Earth? How may the insights gained be received in an unequal context such as present day South Africa? The preceding questions will form the core of the contents of the present investigation.,